Integration of single cell and bulk transcriptomes identifies T cell stress subtypes in LUAD - Shengping Min; Linfeng Pan; Xinyu Zhang; Huili Chen; Lixuan Qiu; Xinyu Wang; Yiluo Xie; Kai Zhang; Qiang Zhang; Chaoqun Lian; Jing Zhang (Discover Oncology)
Abstract Background The unique stress response state of T cells (Tstr) is found in various cancers and correlates with altered Lung Adenocarcinoma (LUAD) tumor microenvironment and immunotherapy outcomes. However, fewer studies have been described on the relationship between Tstr and LUAD, and its mechanism of action in the pathogenesis of LUAD needs to be further investigated. Methods The categorization and validation of cluster types for Tstr signature genes were systematically carried out using transcriptomic data sourced from the TCGA and GEO databases. The focus was on elucidating distinct pharmacological characteristics, tumor microenvironmental traits, and immunotherapeutic benefits across various subtypes. Moreover, a predictive model was developed through Least Absolute Shrinkage and Selection Operator (LASSO) regression analysis, and subsequent cellular experiments confirmed the pivotal role of CREG2 in driving LUAD cell proliferation and migration. Results Tstr signature genes represented by the heat shock protein family are highly expressed at the end of T-cell differentiation and affect cellular communication. Patients with the C1 subtype have a poorer prognosis and high expression of HSPA1A and HSPA1B, which exhibit cold tumor characteristics and define them as important Tstr subtypes. CREG2 is positioned as a promising biological indicator as it plays an important part in enhancing the migratory and proliferative capacity of LUAD cells. Discussion This study reveals the characteristics of different Tstr types. A predictive model was built to forecast the prognosis of LUAD patients based on the DEGs of the subtype. The exploration delved into the bio-function of CREG2 in the progression of LUAD.